2021
DOI: 10.21873/invivo.12292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prognostic Nutrition Index in Gastric or Gastro-oesophageal Junction Cancer Patients Undergoing Nivolumab Monotherapy

Abstract: Background/Aim: We hypothesised that the prognostic nutrition index (PNI) is useful for evaluating host immunity and response to immune checkpoint inhibitors. We investigated the effect of PNI on nivolumab monotherapy efficacy in advanced or recurrent gastric cancer (GC) or gastro-oesophageal junction cancer (GOC) patients. Patients and Methods: We retrospectively examined 110 patients, divided them into a high-PNI group and a low-PNI group, and compared treatment efficacy, adverse events (AEs), and survival b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Five publications showed that PNI was an independent predictor of unfavorable PFS in cancer patients with immunotherapy (18,19,26,27,34), whereas five cohort studies detected no significant relationship between PNI and PFS (20,28,30,31,33). The combined analysis of ten studies that enrolled 1,282 participants showed that a higher PNI level was associated with worse PFS (pHR = 1.61, 95% CI = 1.37-1.88, Figure 3).…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 98%
See 1 more Smart Citation
“…Five publications showed that PNI was an independent predictor of unfavorable PFS in cancer patients with immunotherapy (18,19,26,27,34), whereas five cohort studies detected no significant relationship between PNI and PFS (20,28,30,31,33). The combined analysis of ten studies that enrolled 1,282 participants showed that a higher PNI level was associated with worse PFS (pHR = 1.61, 95% CI = 1.37-1.88, Figure 3).…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 98%
“…Five observational studies reported that PNI was an independent indicator for a shortened OS in cancer patients with immunotherapy (18,19,(26)(27)(28), while PNI was not considered as a prognostic factor for OS in seven studies (20,(29)(30)(31)(32)(33)(34). Pooled analysis of all selected publications revealed that the PNI values higher than the cutoff value predicted a poor OS (pHR = 2.24, 95% CI = 1.57-3.20, Figure 2) in advanced cancer patients treated with immune checkpoint inhibitors.…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 99%
“… 10 Meanwhile, the serum albumin level can reflect the host immunologic status in AGC patients with peritoneal metastases, where cancer progression in the diminished the oral intake, leading to downregulation of the nutritional status of the patient. 11 Thus, there is increasing evidence that the PNI can be an effective prognostic marker, as well as a predictive indicator related to ICIs for various solid tumors. 12 13 14 Accordingly, this study investigated the clinical significance of the PNI for predicting the therapeutic effects of AGC patients with peritoneal metastases treated nivolumab monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Oba et al (17), who found an association between a higher PNI and longer OS (HR=0.27, p=0.0068) in a sample of 60 patients. The PNI has also been described as a useful prognostic marker in patients with other malignant tumors (10,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%